Projeto de produto e produção de galpão industrial pré-fabricado em estrutura de madeira - Vidotti, Luís Henrique Bissi (2018)
The wood, renewable resource, when correctly applied, shows several advantages over other materials used in civil construction and expresses good mechanical properties, low specific weight, and high versatility. The projects generally presented in the civil construction industry are restricted to the characteristics of the product, because they do not contemplate specifications, and orientations directed to the form of production, thus failures are generated in the construction process. Therefore, exposing stage of dimensions, project of buildings with structure and closure in wood, becomes relevant, since the use of the material as a fixed element of construction contributes to increase the sustainability of the works. Demonstrating conception guidelines, and production project model is relevant because of reduction of execution failures generated. So, this research has as study object a timber prefabricated industrial shed. This paper intends to dimension a theoretical model of the object, elaborate the product, and production projects, define concepts and divergences from them. The results established definitions and models of product and production projects, and they pointed out that the reduced elaboration of production projects in the civil construction industry is due to the time spent in the conception, and the singularity between each building.